Construction of a Virtual Simulation Platform for Energy-Saving Technology of Building Envelope Nanostructures (Informatica, 2025)
Aim: In this article, a virtual simulation platform is suggested for the energy-saving technology of building envelope nanostructures to talk about how the thermal performance of building envelopes affects public buildings in a particular area. Methodology: The proposed public building is used as a research subject, and the energy consumption simulation software DeST-c is used to simulate and analyze how the external wall, roof, external window, and enclosure structure with different thermal performance affect the building’s energy use. The different effects of the thermal performance of the building envelope on the cooling and heating loads of the building, as well as the energy-saving potential of the single and whole building envelopes, are analyzed. Results: The results show that the smaller the heat transfer coefficient of the enclosure, the smaller the total annual cumulative load, and the greater the building’s energy efficiency. The energy-saving potential of exterior walls and windows is large, but there are limits, with an upper limit of 20%. The energy-saving potential of roofs is relatively small, with a maximum of 7%. The overall energy-saving potential of the building envelope is great—about 40%. Conclusion: The annual cumulative cooling load of buildings is not significantly affected by the thermal performance of the building envelope. For this area, the effect of improving the envelope’s thermal performance is better in the air conditioning heating season but not obvious in the air conditioning cooling season.